Species-Site Suitability Assessment of Bamboo and Its Detailed Study in Different Agroecological Zones of Kenya - Tarun Kumar Lohani; Gordon Sigu; Nellie Oduor; Selim Reza; Jayaraman Durai (International Journal of Forestry Research, 2023)
The site suitability assessment of Bamboo in Kenya was studied for diverse agroecological zones (AEZs) comprising one indigenous and fifteen exotic bamboo species in nine different AEZs of Kenya. Three bamboo clumps from each species that were at least five years old were assessed to accurately capture data on growth performance and yield. Soil samples collected at 0–30 cm depth from different areas varied considerably. The proportion of soil varied across the bamboo planting sites (F(1,11) = 24.94; p < 0.001), soil pH in the planting sites varied significantly (F(1,11) = 13.92; p < 0.001), and soil bulk densities had different results (F(1,11) = 13.92; p < 0.001). The lowest bulk density (0.61 ± 0.01) was recorded in Kakamega (UM1), while the highest (1.63 ± 0.01) was reported in Gede. Data on characteristics of clumps and internode length and wall thickness integrated through GenStat statistical software using ANOVA entail a huge variation in growth performance for each bamboo species across planting sites. Morphological characters were also studied in detail. The mean height, diameter, and stocking density were comparatively lower even in elevated zones that were only 200 m below its natural range. This resulted in an extremely low yield, which is not viable for economic investment. The species is unsuitable for plantation establishment outside its natural range of 2300 m–3200 m above the sea level (a.s.l.). Plantation below this range will not dissipate but will not attain a healthy growth. The primary use will be restricted for ornamental and conservation purposes such as scaffolding, roof construction, and fabrication of basic household furniture.